Oral Health Status of Pediatric Patients with Autism Spectrum Disorder: A case-control study - Mariela Sosa Seda; Naydi Perez Rios; Sona Rivas Tumanayan; Damaris Molina Negron; Lydia M Lopez del Valle (Revista de Odontopediatria Latinoamericana)
Objective: This study aimed to determine the oral health status and the associated health disparities of pediatric patients with autism spectrum disorder (ASD).